A multivariate and retrospective analysis of the impact of intra-aortic balloon counterpulsation in Open-Heart surgery - Sagar Sharma; Jie Hui Nah; Venkateswaran Siddarth; Haoxing Lai; Shen Liang; Zhi Xian Ong; Duoduo Wu; Haidong Luo; Guohao Chang; Giap Swee Kang; Theo Kofidis; Faizus Sazzad (Scientific Reports)
Abstract Background The use of intraaortic balloon pump (IABP) effectively reduces left ventricular afterload and significantly increases coronary perfusion pressure by raising aortic diastolic pressure. This study examined the short and medium-term outcomes of 22,540 adult cardiac surgical patients requiring an IABP. Methods From 2009 to 2018, 1114 patients (4.94%) undergoing open-heart surgery at a single tertiary cardiac hospital received IABP support and were included in this retrospective study. They were categorized into pre-operative (Group A, n = 577), intra-operative (Group B, n = 475), and post-operative (Group C, n = 62) IABP insertion groups. Results Cardiogenic shock occurred in 11.2% of cases, mainly in Group A. Hemodynamic instability (38.8%) drove IABP use in Groups A and C, while difficulty weaning from CPB was the primary reason in Group C. The overall operative mortality rate was 10.9%, highest at 25.8% postoperatively. Multivariate analysis identified significant predictors of mortality: age (OR: 1.067, 95% CI: 1.041–1.094, p < 0.001), higher BMI (OR: 1.071, 95% CI: 1.017–1.128, p = 0.009), pulmonary hypertension (OR: 2.085, 95% CI: 1.302–3.341, p = 0.002), renal disease (OR: 2.780, 95% CI: 1.556–4.967, p < 0.001), and cardiogenic shock (OR: 3.684, 95% CI: 2.066–6.569, p < 0.001). Complications were more common in Group C, especially with renal disease. Average preoperative and postoperative stays were 4.0 ± 4.8 days and 15.2 ± 20.4 days, respectively, with no significant differences between groups. Conclusion IABP might offer safety for open-heart surgery, with longer hospital stays potentially associated with high-risk patients. Pre-operative IABP prophylaxis could be crucial in high-risk open-heart cases to reduce mortality. Clinical registration number: NHG DSRB Ref No# 2016/01070 and 2019/00397.